2011
DOI: 10.1681/asn.2010111160
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Calcineurin-Inhibitor-Sparing Regimens in Kidney Transplantation

Abstract: Calcineurin-inhibitor-sparing strategies in kidney transplantation may spare patients the adverse effects of these drugs, but the efficacy of these strategies is unknown. Here, we conduct a meta-analysis to assess outcomes associated with reducing calcineurin inhibitor exposure from the time of transplantation. We search Medline, Embase, and Cochrane Register of Controlled Trials for randomized controlled trials published between 1966 and 2010 that compared de novo calcineurin-inhibitor-sparing regimens to cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
84
3
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(91 citation statements)
references
References 68 publications
(30 reference statements)
2
84
3
1
Order By: Relevance
“…Although CNIs are associated with renal injury, whether acute or chronic, many trials to minimize or even avoid CNIs, particularly cyclosporine, have been conducted (51,(67)(68)(69)(70)(71)(72)(73)(74).…”
Section: Cyclosporine Versus Tacrolimusmentioning
confidence: 99%
See 2 more Smart Citations
“…Although CNIs are associated with renal injury, whether acute or chronic, many trials to minimize or even avoid CNIs, particularly cyclosporine, have been conducted (51,(67)(68)(69)(70)(71)(72)(73)(74).…”
Section: Cyclosporine Versus Tacrolimusmentioning
confidence: 99%
“…A recent meta-analysis compared CNI-sparing regimens, either through complete avoidance or minimization, to the standard of care, which is CNI-containing regimens (74). Although the 17 minimization studies, which included 4131 patients, showed no difference in acute rejection, CNI-minimizing regimens showed a reduction in graft failure (odds ratio, 0.73; 95% confidence interval, 0.34-1.31).…”
Section: Cyclosporine Versus Tacrolimusmentioning
confidence: 99%
See 1 more Smart Citation
“…In their meta-analysis, Sharif et al found that CNI-sparing strategies are associated with less delayed graft function, improved graft function and less NODAT (ref. 33 ). Tacrolimus has usually been observed to be more diabetogenic 6 .…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%
“…Some but not all trials demonstrated better renal function (eGFR) with CNI minimization, perhaps slight improvement in some CNI-specific adverse events, but none showed improved patient or graft survival. 9,10 It seems increasingly evident that many of these trials were based on a false premise: that CNIs were the principal cause of chronic graft dysfunction. [11][12][13] As our understanding of late graft dysfunction evolved to recognize a critical role for antibody-mediated injury, it is ironic that evidence of the importance of antibody emerged in part from studying the impact of CNI withdrawal or avoidance.…”
mentioning
confidence: 99%